The Co-Parental Divorce: Removing the Children from the Jurisdiction - Payne, Julien; Overend, Eileen (Revue générale de droit, 1984)
The preservation of parenting rights in contested custody or access proceedings arising on the dissolution of marriage necessitates a judicial reconciliation or balancing of the competing interests of the children, the parents and members of any extended or reconstituted families. In C. v. C., (unreported, March 7, 1984, Ont. S.C.) the mother was held to the terms of a prior separation agreement and was ordered not to remove the children from the Province of Ontario without the father's consent or a further order of the court. In reaching this decision, the trial judge placed heavy reliance on the evidence of a mediator who had unsuccessfully attempted to resolve the differences between the parents and who was of the opinion that the children would be at risk if the mother proceeded with her plans to remarry and establish a new home for herself and the children in England. C. v. C. raises diverse fundamental issues concerning the legal resolution of parenting disputes on marriage breakdown or divorce. The following issues are addressed in the commentary of this judgment (reproduced in annex): 1. What significance, if any, does, and should, a court give to the express terms of a separation agreement? 2. If a mediator is retained, should the mediation process, including the mediator's evaluation, be “open” (i.e. subject to disclosure to the court) or “closed” (i.e. confidential and excluded from any evidence adduced in subsequent judicial proceedings)? 3. How can the best interests of the children — the legal criterion to be applied in the adjudication of parenting disputes — be reconciled with the best interests of other concerned family members? 4. Could, and should, the court have addressed the possibility of some alternative form of parenting arrangements that might accomodate the competing interests of all the affected parties? 5. To what extent can the courts legally fetter the freedom of a custodial parent to establish a new home for (i) herself (or himself) and (ii) the children? Some of these issues are specifically addressed in the unreported reasons for judgment. Others are ignored. The purpose of this commentary is to canvass these issues and point to the need for a family-oriented approach to the resolution of parenting disputes, rather than an individual rights approach, such as has been traditionally adhered to by the courts in the adjudication of custody and access disputes.